Kajian Teologis Sembahyang Senja dan Sembahyang Singsing Fajar dalam Gereja Ortodoks Timur - Tjong, Andrew Lucas; Wicaksono, Yohanes Bambang Cahyo (JURNAL ILUMINASI, 2025)
The liturgy of the Eastern Orthodox Church embodies a profound richness of symbolic and theological meaning, particularly in the services of Esperinos (Vespers, Evening Prayer) and Orthros (Matins, Dawn Prayer), celebrated both daily and in anticipation of the Lord’s Day (Sunday). This article specifically explores the theological significance of these two liturgical hours. Employing a historical-theological approach rooted in patristic writings, alongside dogmatic theology through the study of Orthodox liturgical texts, this study highlights how these hours shape the spiritual life of Orthodox Christians. Esperinos marks the transition from evening to morning, echoing the biblical narrative of creation and the eschatological hope for divine light. Orthros, celebrated before sunrise, symbolizes Christ’s resurrection and proclaims the dawn of the new era, the age of grace and salvation manifested in the light of Christ. These services are not mere liturgical formalities, but serve as a medium of apostolic kerygma that forms the faith consciousness and spirituality of the faithful. This article also opens space for ecumenical dialogue within the Indonesian Christian context, particularly in enriching the understanding of worship as the heart of ecclesial life oriented toward the mystery of salvation.